Estabilidade Linear no Problema de Robe - NASCIMENTO, Francisco José dos Santos (2017)
In this work, we discuss the article The Existence and Stability of Equilibrium Points in the Robe Restricted Three-Body Probem due to Hallan and Rana. For this we present some basic definitions and results abut Hamiltonian systems such as equilibrium stability of linear Hamiltonian systems. We set out the restricted problem of the three bodies and show some classic results of the problem. Finally we present the Robe’s problem and discuss the main results using Hamiltonian systems theory.